Uterine necrosis in a case of B-Lynch brace suture - Satia, Meena N.; More, Vibha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
B Lynch is a conservative surgical procedure for Atonic PPH not responding to medical line of treatment very few complications of this procedure have been reported. We describe B-Lynch suture erosion through the uterine wall identified on 16 day postpartum. A 24 year old primigravida underwent a primary low transverse cesarean section at term indication being primigravida with breach presentation intra-operatively there was torrential blood loss and uterus remained flabby despite treatment with uterotonics drugs delayed absorbable suture was used to place B-Lynch suture for control of the hemorrhage and had sepsis for which she had to undergo obstetric hysterectomy.